An Encounter Between Two Frente Populares? Diplomatic Relations Between the Spanish Republic in War Time and the Chilean Republic (1931-1940) - De La Llosa, Alvar (Revista de Historia Social y de las Mentalidades, 2018)
This article tries to understand, from an international relations approach, the exchange of models and the possibility of a political influence of the Spanish Republican Embassy in Santiago de Chile in the building of the Chilean Frente Popular, and the reasons of its development inside the complex issue of international diplomatic relations for a country in war in search of allies. The question at hand is whether these relations were dominated by the diplomatic tradition of exchange or by a sense of ideological solidarity. The study of diplomatic documents -be they Spanish or French- clearly reveals that although diplomatic relations were a priority, nevertheless a transfer of experiences in organization as well as financial support existed. It also sheds a light on the modalities of this aid.